Simulating particle sedimentation in a flowing fluid using an immersed boundary–lattice Boltzmann method. Issue 1 (2nd January 2020) - Liu, Shenggui; Tang, Songlei; Lv, Mindong; Zhao, Yuechao; Li, Yingjun
ABSTRACT: A combination of the lattice-Boltzmann and immersed-boundary methods is used to simulate the behaviour of circular particles in fluids, including their behaviour in stationary and flowing fluids. This method simulates the fluid domain with a regular Eulerian grid, and the non-grid uniform boundaries with a Lagrangian grid. The no-slip boundary condition of the fluid and particle boundaries is enforced by interpolating boundary forces. This simulation uses a direct-force method to achieve a slight deformation of solid particles. The correctness of the method is validated using simulations of the flow past an impulsive cylinder. Finally, the method is used to compare the particles' behaviour in stationary and flowing fluids. The result shows that a well-known 'drafting, kissing, and tumbling' (DKT) case occurs in the particle sedimentation in the stationary viscous fluid. In contrast, kissing occurs in the moving fluid, but no separating.